2004
DOI: 10.1186/1471-2180-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Mycoplasma pneumoniae P1 and P116 in patients with atypical pneumonia analyzed by ELISA

Abstract: Background: Serology is often used for the diagnosis of Mycoplasma pneumoniae. It is important to identify specific antigens that can distinguish between the presence or absence of antibodies against M. pneumoniae. The two proteins, P116 and P1, are found to be immunogenic. By using these in ELISA it is possible to identify an immune response against M. pneumoniae in serum samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The ELISA for Campylobacter jejuni , Salmonella enteritidis and human HSP60 were performed as described [22]. ELISA plates were coated with 4 µg/ml human HSP60, C. jejuni HSP60 or S. enteritidis HSP60.…”
Section: Methodsmentioning
confidence: 99%
“…The ELISA for Campylobacter jejuni , Salmonella enteritidis and human HSP60 were performed as described [22]. ELISA plates were coated with 4 µg/ml human HSP60, C. jejuni HSP60 or S. enteritidis HSP60.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the advent of antibiotics and vaccination, it was a leading cause of mortality ( 1 , 5 ). At present, the most common bacterial causes of pneumonia are the so-called atypical bacteria, Mycoplasma pneumoniae and Chlamydophila pneumonia ( 7 ). Legionella pneumophila is also considered atypical; however, it is less common ( 1 , 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic process of all types of pneumonia is able to cause acute or chronic inflammation in the mediastinal lymph nodes, lymph node hyperemia edema, hyperplasia of lymphocytes and macrophages, and infiltration of neutrophils, monocytes, and plasma cells ( 7 , 10 ). In addition, the lymph nodes may experience necrosis and granuloma formation ( 7 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic properties of recombinant proteins P116 and P30 have also been shown [15,18,19]. A combination of frequently recognized antigens could be useful for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have reported great interest in using a recombinant protein corresponding to the C-terminal portion of the P1 adhesin, which has been described as the immunodominant antigen in M. pneumoniae [ 2 , 13 - 17 ]. Antigenic properties of recombinant proteins P116 and P30 have also been shown [ 15 , 18 , 19 ]. A combination of frequently recognized antigens could be useful for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%